Examining Farmers’ Marketing Practices in the Fresh Fruits and Vegetables (FFV) Industry - Arumugam, Nalini (2010)
This study is to examine the farmers’ marketing practices in the fresh fruits and vegetables (FFV) industry. It aims firstly, identifies the current marketing practices of FFV; secondly to determine the factors which motivate contract farmers to participate in contract farming; thirdly to identify the determinants of FFV farmers participating in contract farming and lastly to evaluates the nature of sourcing and procurement practices by FFV buyers (with a special focus on hypermarkets). The study utilizes both quantitative and qualitative research. The study was conducted a survey on FFV farmers by using a structured questionnaire. The survey was conducted from April 2007 to July 2007 in populous states namely Kedah,Kelantan, Terengganu, Pahang, Perak, Selangor and Johor in Peninsular Malaysia. The study utilized a random sampling method. A total of 208 FFV farmers were interviewed. One hundred and sixty seven FFV farmers were independent farmers and the remaining were contract farmers. As for the qualitative research, an in-depth interview was conducted with FFV buyers which include Malaysian Agrifood Corporation (MAFC), Mydin, Giant, ECONSAVE and UO Superstore to get insights on FFV buyers sourcing and procurement practices. Factor analysis was carried out to identify latent factors that influenced FFV farmers in their participation in contract farming. The factor analysis uncovered five factors,as perceived by the FFV farmers, as reasons for their involvement in contract farming. These factors are: market assurance, access to marketing information and technology, transfer of technology to improve farming practices, access to inputs and indirect benefit. These factors, in sum, explained 76.8 per cent of the variance in the farmers’ decision-making process. The FFV contract farmers also agreed that the new approach in marketing their produce not only increased their income and knowledge but also enhanced their productivity. Logit analysis uncovers seven determinants of FFV farmers’ participation in contract farming. It was found that land ownership, farm size, education and perceived benefit were four determinants that positively influenced farmers’ participation in contract farming. Complicated process, lack of opportunities and price risk were three determinants that negatively influence the farmers’ participation in contract farming. Several forms of sourcing and procurement practices for FFV produce were observed among the FFV produce buyers. These practices included: 1) Lead or large scale FFV farmers deliver FFV produce directly to supermarkets; 2)wholesalers directly deliver to supermarkets and 3) supermarkets’ use of specialized sourcing and procurement agency such as FAMA. It was observed that supermarkets or hypermarkets do not have any contract agreement directly with farmers as well as any written document. FFV farmers deliver by arrangement. By buying directly from FFV farmers, supermarkets or hypermarkets by pass the middleman, enable them to obtain the supplies in cheaper prices. Supermarkets or hypermarkets buy in bulk and secured their supplies from wholesale market. This was mainly due to wholesalers’ ability in supplying in bulk as well as deliver in the right time and quality. Buyers’criterions in choosing suppliers were volume, price, quality and formed relationship of trust.